Español: Español (OdontoInvestigación, 2022)
Knowledge of the internal root anatomy and its different configurations is of great importance to guarantee a correct procedure and achieve a successful endodontic treatment. The aim of this study is to document two clinical cases of lower premolars with different anatomical characteristics. In the first case, a type VIII lower first premolar is evident according to the Vertucci classification, with an incidence of 0.5%. While, in the second case, a type IV lower first premolar is observed according to the Vertucci classification, with an incidence of 24%.
Keywords: Spanish